Is What Low-Income Brazilians Are Eating in Popular Restaurants Contributing to Promote Their Health? - Carrijo, Alinne de Paula (Nutrients, 2018)
This study evaluates the healthfulness of the meals offered to and consumed by low-income Brazilians in Popular Restaurants (PR). It is a cross-sectional, exploratory study. The final sample includes 36 PRs, respecting the stratification criteria for each of the five Brazilian regions. To identify the quantity and quality of food consumption, consumers’ meals are evaluated. The sample calculation uses a minimum of 41 consumers in each PR. Consumption evaluation is carried out by weighing and direct observation of the meal that each consumer served to his plate. Each dish of the meals had its Technical preparation files (TPF) developed by observing the production and weighing all the ingredients. Evaluations of Energy density (ED), meal’s weight components and sodium composition are conducted. Plate’s composition is compared to “My plate” guidelines United States Department of Agriculture (USDA). The final sample includes 1771 low-income Brazilians consumers. The plate of PRs consumers is adequate only for the “protein group” in comparison to “My plate”. Rice and beans compose more than 50% of the plate’s weight, as expected, since it is a Brazilian habit of consumption at lunch. Thus, grains are the major group consumed by PRs consumers. The average ED for all PRs is 1.34 kcal/g. Regarding sodium content, rice and main courses presented the highest values and are classified as high, according to Food and Drug Administration (FDA). Concerning sodium, PRs are putting Brazilian low-income population at risk for chronic diseases. However, in general, PRs are good choices because they promote access to cheap and quality traditional Brazilian foods.